Identifying Critical Factors for Sustainable Tourism and Local Community Development: Evidence from Select Destinations in Bangladesh - Dhanonjoy Kumar; Norhayah Zulkifli; Nilanjan Ray (Centre For Tourism Planning and Development, 2023)
Tourism has always acts as a catalyst to develop local economy, improve socio-cultural changes and life style of the people residing tourist destinations. To conduct this study 616 respondents were selected from Khulna, Jessore, Bagerhat, and Kushita. On the other hand, Socio-cultural condition are influencing for development of local destinations. This paper argues and figures out influential factors of Socio-cultural condition by its broader societal context for more effective policy making. The purpose of this study is to assess the critical factors for sustainable tourism and community development of the local tourism industry in Bangladesh, to identify the major challenges in the local tourism sector in Bangladesh , to provide necessary suggestions for ensuring the sustainable development of the local tourism sector in Bangladesh. For fulfillment of above stated objectives data has been collected from various stakeholders and selected statistical techniques, such as measurement models, discriminant validity, and hypothesis testing were employed to examine the data in the study to confirm the study's assumption through SPSS and AMOS. The study is particularly important from a practical standpoint since it outlines difficulties and methods for the development of Bangladesh's tourist industry, which should be a priority in the development process. These characteristics can be applied to the local and worldwide development of a tourist location.